Cooperation in Digital Innovation Under the Master Plan on Asean Community (MPAC) in Muslim Asean Countries - Susilo, Joko (Airlangga Journal of Innovation Management, 2024)
This study examines the present conditions and obstacles faced by digital innovation in Indonesia and Malaysia, explicitly focusing on Muslim ASEAN countries. Additionally, it seeks to identify potential areas for collaboration and cooperation within the framework of the Master Plan on ASEAN Connectivity (MPAC) in Digital Innovation, such as the Quick Response Indonesian Standard (QRIS) in Indonesia and Malaysia. Besides, this qualitative study employed a literature review. In addition, the collaboration between Indonesia and Malaysia on the Master Plan on ASEAN Connectivity (MPAC) in Digital Innovation, particularly in Quick Response Indonesia Standard (QRIS), can significantly improve economic integration and social growth in Muslim ASEAN nations. The result of this study is that Through the implementation of QRIS. This digital payment system makes use of QR codes to carry out transactions across international boundaries, reducing the costs of transactions. According to the author, this study is a first attempt to build a factual and theoretical basis for the researcher's analysis of the cooperation on the Master Plan on ASEAN Connectivity (MPAC) in digital innovation in Muslim countries in the ASEAN region, including Indonesia and Malaysia.